Etiological agents in Chronic Suppurative otitis Media - Abdul Khader, Karnul; Parihar, Harlal; Kumar Mishra, Rakesh (International Journal of Medical Research and Review, 2014)
Introduction: Chronic suppurative otitis media is an important cause of preventable hearing loss, particularly in the developing world. It is characterized by recurrent discharge from middle ear cavity through perforated tympanic membrane. Prevalence varies from eastern world when compare with western hemisphere. Most of the organisms are resistant to various antibiotics. We have conducted this study to identify etiological organism. Methods: This study was a case control analysis study conducted in tertiary care teaching hospital of Central India after taking permission from Institutional Research board [IRB]. Total duration of study was 2 years. 216 patient’s patients who came to OPD or admitted in hospital for chronic ear discharge & full fill inclusion criteria have been included in study. Results: Out of 216 patients 119 (55 %) were male & 97 (45 %) were female. Staphylococcus (25 %, n= 55) & Pseudomonas (26 %, n=56) together were two most common organisms comprised nearly fifty percent of total patients. Nearly 30 % of culture did not reveal any growth. Candida was most common fungus on culture comprised nearly 7 % of total population. Conclusion: Sensitivity pattern varies with geographical areas but most of the organisms are sensitive with ciprofloxacin ear drops. It is consider first line of drugs for CSOM.